The use of institutional theory in social and environmental accounting research: a critical review - Eitrem, Anna; Meidell, Anita; Modell, Sven (Taylor & Francis, 2025)
In this paper, we review and critique the use of institutional theory in social and environmental accounting (SEA) research and discuss whether this has helped or hindered in furthering a critical research programme that is concerned with questions of power and emancipation. This research focus is warranted by broader debates within institutional theory as well as the SEA literature. Insofar as institutional theory is concerned, there are disagreements as to whether this theory can be imbued with critical intent or whether it is trapped in a normal science tradition of constantly extending and refining theory that detracts from such intent. By contrast, within the SEA literature, we find a largely inverse criticism suggesting that its lack of theoretical sophistication has diminished its critical potential. We show that most institutional research on SEA under review has not advanced research in a critical direction. However, this has little to do with the normal science ideal underpinning institutional theory but is rather due to the failure to keep up with key conceptual developments crystallising its critical potential. We outline a research agenda that may turn institutional research on SEA into a more critical research programme while simultaneously developing institutional theory conceptually.